Boston Naming Test: Lose the Noose. (5th April 2021) - Eloi, Janelle M; Lee, Jennifer; Pollock, Erica N; Tayim, Fadi M; Holcomb, Matthew J; Hirst, Rayna B; Tocco, Carly; Towns, Stephanie J; Lichtenstein, Jonathan D; Roth, Robert M
Abstract: Objective: Administering the noose item of the Boston Naming Test (BNT) has been questioned given the cultural, historical, and emotional salience of the noose in American culture. In response, some have modified the BNT by skipping/removing this item and giving the point as if the examinee responded correctly. It is unknown, however, whether modifying standardized administration and scoring in this manner affects clinical interpretation. In the present study, we examined the prevalence of noose item failure, whether demographic and clinical characteristics differed between those who responded correctly versus failed the item, and whether giving a point to those who failed affected clinical interpretation. Method: Participants included a mixed clinical sample of 762 adults, ages 18–88 years, seen for neuropsychological evaluation at one of five sites within the USA. Results: Those who failed the item (13.78%) were more likely to be female, non-White, and have primary diagnoses of major neurocognitive disorder and epilepsy. Noose item failure was associated with lower BNT total score, fewer years of education and lower intellectual functioning, expressive vocabulary, and single word reading. Giving a point to those who failed the item resulted in descriptor category change for 17.1%, primarily for patients with poor overall BNT performance. Conclusions: Only a small percentage of patients fail the noose item, but adding a point for these has an impact on score interpretation. Factors associated with poorer overall performance on the BNT, rather than specific difficulty with the noose item, likely account for the findings.